Combination antifibrotic and immunosuppressive therapy in progressive fibrosing ILD - Fischer, Ryan; Abdul Rehman, Khawaja (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background: Progressive fibrosing interstitial lung disease is characterized by continuous functional decline and early mortality despite conventional immunosuppressive therapy. The dual pathophysiology involves both inflam-mation and fibrosis and provides rationale for combination antifibrotic and immunosuppressive therapy. Objectives:To review and synthesize current clinical evidence on the efficacy, safety, and clinical positioning of combination antifibrotic and immunosuppressive therapy in progressive fibrosing interstitial lung disease.Methods: We conducted a comprehensive literature review of randomized controlled trials, observational studies, and real-world cohorts published between 2015 and 2025 that evaluated combined antifibrotic (nintedanib or pirfe-nidone) and immunosuppressive therapy in adults with non-IPF progressive fibrosing ILD. We synthesized  evidence from randomized controlled trials, observational studies, and real-world data regarding their methodolo-gies, patient population, therapies and outcomes.Results: Forty-one studies were identified, including 14 RCTs and 12 observational cohorts. The available evidence suggests that combination therapy demonstrates promising results across various PF-ILDs. Clinical trials and real-world data have shown improved lung function and forced vital capacity with combination therapy in PF-ILD. Evi-dence supports combination therapy to be well-tolerated, with manageable safety and tolerability profile consistent with individual agents rather than additive effects. Limitations of the available evidence include heterogeneity of PF-ILD populations, variable background immunosuppression, and limited long-term outcome data.Conclusions: Combination antifibrotic and immunosuppressive therapy shows meaningful efficacy in select PF-ILD patients. Evidence supports individualized combination approaches, particularly for progressive systemic sclerosis-ILD and connective tissue disease-ILD with nonspecific interstitial pneumonia pattern. Critical evidence gaps remain regarding optimal sequencing, patient selection, and long-term outcomes, requiring future investigation.